Extension Education: Myth or Reality - Das, Samares Kumar; Tripathi, Hema (International Journal of Bio-resource and Stress Management, 2023)
Extension Education (popularly known as Agricultural Extension) is a science and art of ‘helping people help themselves’ in shaping their behavior in desirable direction based on the philosophy and principle of ‘learning by doing’ and ‘seeing is believing’. There are several branches of Extension Education-veterinary and animal husbandry extension, fishery extension, home science extension, forestry extension, health extension and the like-depending on the field where the philosophy and principles of Extension Education is applied. As per the philosophy, an Extension Educator should be a teacher, guide, friend and philosopher to the villagers. But, there is a gap between the philosophy and practice, between what is and what ought to be. Mixed farming system based on the socio-economic and cultural considerations is the foundation of Indian agriculture. Under this traditional family farming system animal husbandry has a complementary and supplementary relationship with crop husbandry the significance of which is never realized in the practice of Extension Education. The crux of the problem lies in the practice of viewing crop and livestock separately at par with the western specialized farming. The tendency of perceiving Indian agriculture from the western perspective is not going to bring any desirable change in our countryside. It is high time to bring science down to the ploughman’s doorstep to help him taking timely and wise decision to improve his farm and home in a sustainable manner. To achieve this we need a large number of philosophers in ‘helping people help themselves’ in shaping their behavior in desirable direction. This paper is an attempt towards that direction.